ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP PEMILIK AKUN INSTAGRAM YANG MENGANDUNG KONTEN PORNOGRAFI BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI - Simamora, Desvi Christina; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The development of science and technology sangantlah rapidly in people's lives and nation. As one example of the development of science and technology in the field of multimedia telekomonikasi is instagram account. Namely, as the account serves as a medium for memermudah someone to create a picture / video and send in time epat, but the benefits of information and communication technology is widely used by people who are not responsible for committing new crimes (cybercrime) in the form of information dissemination in the form of pornographic content. Though the impact of pornography increasingly clear is the effect of which is often the case of adultery, rape, and even murder and abortion. With the misuse of technology in social media, it has caused a crime called Cyberporn. Based on this understanding, the writing of this formulation formulated two issues namely; The first, How criminal liability against the owner of the account instgram containing pornographic content based on Law Number 44 Year 2008 on pornography. Second, how the implementation of criminal liability against the owner instagram account that contain pornographic content based on Law Number 44 Year 2008 on pornography .This types of research can be classified in normative research, because this research was conducted by examining secondary data as well as the approach of the legislation, normative research examines the legal principles contained in Law No. 44 Year 2008 on Pornography. Specifically regarding criminal responsibility. The data sources used, the primary data, secondary data, the data tertiary data collection techniques in this study is normative, the data used is the study of literature. After the data collected then analyzed qualitatively, then draw conclusions with a method of thinking deduktitf is to analyze the problems of the general form into special shapes From the research, there are two basic problems that can be inferred, first, Criminal Liability Against Own Instagram account Containing Pornography Content Based on Law No. 44 Year 2008 on Pornography. Second, implementation of Criminal Liability Against Own Instagram accounts that contain pornographic content based on Law Number 44 Year 2008 on pornography.Keywords: Criminal Liability - Crime - Pornography